Bioentrepreneur to Grow Biology Students' Creativity UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Hotmaidah Hasibuan; Silvia Ardina Siregar (Institut Agama Islam Negeri, 2023)
Student creativity can be developed through entrepreneurial activities (bioentrepreneur) by utilizing herbal ingredients that have good health benefits. Student awareness for entrepreneurship is also supported by seeing the difficulty of getting jobs after graduating from university. This creativity development trains students in the urban farming entrepreneurship course by utilizing campus land in the city to remain entrepreneurs (preneurs), so that the perspective of students seeing job opportunities in the future is not looking for work but creating jobs. This study aims to describe comprehensively about fostering the entrepreneurial spirit of biology students (bioentrepreneurship). The research population was all 42 students in the biology education study program in semesters 4 and 6 of the FTIK UIN SYAHADA Padangsidimpuan, totaling 42 people. Sampling in this study was carried out by means of random sampling with a total sample of 20 people. This type of research is qualitative. The data collection technique was carried out by distributing questionnaires online using the Google form application. Data analysis techniques using qualitative analysis. The results showed an interest in entrepreneurship for students of the Tadris Biology Study Program at the State Islamic University of Syekh Ali Hasan Ahmad Addary Padangsidimpuan based on an average score of 5 indicators, namely being at high criteria. The conclusion of the study is that there is a high interest in entrepreneurship after attending an urban farming entrepreneurship class. Recommendations aimed at students are expected to be able to apply entrepreneurial indicators and participate in entrepreneurial activities outside of the course with the aim of being able to foster interest in creating their own business.